Impaired washout - embolism and ischemic stroke: further examples and proof of concept - Sedlaczek, Oliver; Caplan, Louis R.; Hennerici, Michael G. (Cerebrovascular diseases, 2005)
We previously posited that impaired washout of emboli was an important mechanism of brain infarction in patients with cerebral hypoperfusion. Hyperviscosity and hypoperfusion enhance thrombus formation promoting embolization of fresh thrombi. Hypoperfusion also reduces dissolution of emboli due to reduced flow velocity leading to classic hemodynamic patterns of stroke. To prove this concept further, we identified patients with severe hemodynamic compromise of either arterial or venous origin, or both, and natural or iatrogenic mechanisms of embolism. Three conditions were investigated in a stroke MRI protocol: 5 patients who had conventional cerebral angiography for the diagnosis of moyamoya disease, 1 patient with atrial fibrillation and thrombosis of the left transverse dural sinus and 1 patient with a patent foramen ovale with atrial septum aneurysm presenting with thrombosis of cortical cerebral veins. In all patients, subcortical arterial embolization within an atypical borderzone of hypoperfusion was observed.